2016
DOI: 10.3846/btp.2016.554
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Forecasting with Information Flow Approach

Abstract: and increasing international trade turnovers lead to great demand for exchange rate forecasts. On the other hand, the amount of factors which influence the fluctuations of exchange rates, the heterogeneity of market participants, the amount of financial instruments which allow to gain exposure to a particular currency and the organizational form (over the counter system) of the market complicate the process of generating exchange rate forecasts.In the second part of 20th century there were many exchange rate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Yeh-Yun Lin and Edvinsson (2008) compare the Nordic countries in terms of their national intellectual capital. Mačerinskienė and Balčiūnas (2016) investigate exchange rate forecasting using an information flow approach, offering empirical evidence from Lithuania. Salonius and Lönnqvist (2012) assess the policy relevance of national intellectual capital information, evaluating its usefulness for decision-makers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeh-Yun Lin and Edvinsson (2008) compare the Nordic countries in terms of their national intellectual capital. Mačerinskienė and Balčiūnas (2016) investigate exchange rate forecasting using an information flow approach, offering empirical evidence from Lithuania. Salonius and Lönnqvist (2012) assess the policy relevance of national intellectual capital information, evaluating its usefulness for decision-makers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additional drivers for economic expansion through competitiveness, particularly in service-oriented sectors such as tourism, would be described as follows: a highly and relevantly knowledgeable workforce that, combined with the appropriate infrastructure, can transform and accumulate unsalable surplus knowledge overs; knowledge capital (Bérubé and Mohnen, 2007). A study by (Oprescu and Oprescu, 2012) linking knowledge-based capital to national economic growth, equivalent research aiming to link wealth and/or national competitiveness was published by (Bontis, 2004 Mačerinskienė and Balčiūnas, 2016). Several studies attempt to understand the dynamics of intellectual and knowledge capital at the national level, while others focus on how national knowledge capital can be optimized and managed to spur progress in trade and industry (Roos, 2017).…”
Section: National Prosperitymentioning
confidence: 99%
“…The introduction of the microstructure approaches brought dramatic developments in short run horizon and has a significant impact on the exchange rate dynamics. The literature showed that the microstructure approaches to exchange rates have achieved substantial improvements due to the availability of high quality and high frequency data [4,5]. Moreover, besides the microstructure fundamentals, the commodities prices have also considered as an important determinant of the exchange rate in export oriented economies.…”
Section: Introductionmentioning
confidence: 99%